Enhancing Public Relations in the Tourism Industry: A Case Study of Sulaimani Hotels (Raparin Journal of Humanities (RJH), 2025)
Region, The aim of this study is to explore how Public Relations can enhance tourism services in the Kurdistan specifically focusing on guest satisfaction with public relations staff and the quality of hotel services in Sulaimani city. This research evaluates aspects such as (service styles, accommodations, foods and drinks) within hotels in the Sulaimani. The study is stands out to be one of the most descriptive studies that have been used to achieve its goals. Also, the study included tourists who visited hotels in Sulaimani city. The research focuses on the five-star hotels in this city of Sulaimani to benchmark service quality. The research underlines the significance of tourism for the Kurdistan Region especially in Sulimani city, highlighting its potential as a key income source and a driver of economic development.It also contributes to theoretical and academic knowledge about the role of Public Relations in enhancing tourism professionalism. The key outcomes are reveal that the Public Relations staffs in Sulaimani hotels excel in providing courteous and welcoming service. The quality of hotel services, including accommodations, foods, and beverage provisions, is notably high. Furthermore, the hotels are well-equipped with communication services, information technology, and recreational facilities like swimming pools and gyms.